Accent Stabilizes 1:2 Sensorimotor Synchronization of Rhythmic Knee Flexion-Extension Movement in Upright Stance - Etani, Takahide; Miura, Akito; Okano, Masahiro; Shinya, Masahiro; Kudo, Kazutoshi (Frontiers in Psychology, 2019)
Numerous studies have shown the importance of metrical structure on beat perception and sensorimotor synchronization (SMS), which indicates why metrical structure has evolved as a widespread musical element. In the current study, we aimed to investigate the effect of metrical structure with or without accented sounds and the alignment of accent with flexion or extension movements on the stability of 1:2 SMS in rhythmic knee flexion-extension movement in upright stance (flexing the knee once every two sounds). Fourteen participants completed 1:2 rhythmic knee flexion-extension movements with a metronome beat that accelerated from 2 to 8 Hz (the frequency of the movement was 1–4 Hz). Three sound-movement conditions were provided: (1) combining the flexion phase with loud (accented) sound and the extension phase with soft (non-accented) sound, (2) the reverse combination, and (3) combining both movements with loud sound. ANOVA results showed that metrical structure with accented sounds stabilizes 1:2 SMS in the range of 3.5–7.8 Hz in terms of timing accuracy, and flexing on the accented sound is more globally stable (resistant to phase transition) than flexing on the non-accented sound. Furthermore, our results showed that metrical structure with accented sounds induces larger movement amplitude in the range of 4.6–7.8 Hz than does that without accented sounds. The present study demonstrated that metrical structure with accented sounds stabilizes SMS and induces larger movement amplitude in rhythmic knee flexion-extension movement in upright stance than does SMS with sequences without accents. In addition, we demonstrated that coordinating flexion movement with accented sound is more globally stable than coordinating extension movement with accented sound. Thus, whereas previous studies have revealed that metrical structure enhances the timing accuracy of SMS, the current study revealed that metrical structure enhances the global stability of SMS.